Quilting Mystery : Knot Ready for Murder - Book 9 - Marks, Mary (New York : Kensington Books, 2021)
Before quilter Martha Rose can tie the knot to Crusher, she has to track down his missing first wife... One loose thread threatens to unravel Marthas wedding plans: the groom-to-be married a pregnant teen to save her from scandal thirty years ago--and the marriage was never annulled. Now Crushers wife Hadas is coming to LA, along with his sister Fanya. But soon after she arrives, their houseguest goes missing, with her room ransacked and a chloroform-soaked cloth left behind. Could her apparent abduction be connected to her brothers unsolved death from a hit-and-run six months ago? Martha and her quilting cohorts must find the pattern to solve the twin mysteries and determine if Crusher is still married--or now a widower...
Keywords: Rose, Martha -- (Fictitious character) -- Fiction; Retired women -- Fiction; Quilting -- Fiction; Remarriage -- Fiction; Weddings -- Fiction; Kidnapping -- Investigation; Fiction; Cozy mystery fiction